How the internet supports the consumer decision process: the case study of McCarthy Call-a-Car - Limbada, Suhayl (Rhodes University, Faculty of Commerce, Department of Management, 2006)
This thesis aims to provide a better understanding of the ways in which the Internet supports the consumer decision process of potential customers in an online car retail environment. The thesis is mainly focused on how this can be done in South Africa. A case study approach was adopted in investigating the case of McCarthy Call-a-Car. Interviews were carried out with McCarthy Call-a-Car employees and documents and the Call-a-Car website, were analysed. It was revealed that Call-a-Car focuses on using the Internet to support customers in the pre-purchase phase only. The purchase and post-purchase phases are carried out offline at its dealership network and Club McCarthy respectively. The findings showed that Call-a-Car views the Internet as a marketing tool that provides convenience to customers searching for product information in the pre-purchase phase. The interviews revealed that due to Call-a-Car's strategy, as well as practical problems of selling online, the customer will still have to visit a dealership to conclude a purchase and for post-purchase support. From this research it appears that there are three main issues arising out of Call-a-Car's usage of the Internet in the customer buying process: firstly, the research revealed that instead of cutting out the middle-man, the Internet has created new types of intermediaries called "cybermediaries" and that Call-a-Car is one such intermediary. Secondly, it was revealed that trust is crucial in the online environment and that Call-a-Car builds trust through branding. Thirdly, the Internet has not affected prices online, despite theoretical estimations that the Internet would induce lower prices. The main recommendations for future research are empirical studies to investigate if the cybermediary model is unique to the car industry and whether this business model could be applied to other look and feel industries such as real estate. Future studies could also investigate the mechanics of trust-building and brand-building in the online environment and finally, studies from the customer perspective considering what Internet tools the customer would like to see online to support them during their buying decision process.
Keywords: McCarthy Call-a Car; Automobile dealers -- South Africa; Automobile industry and trade; Internet marketing; Consumer behavior; Customer services; Consumer satisfaction